Top-down modulation of dichotic listening affects interhemispheric connectivity: an electroencephalography study - Elyamany, Osama; Iffland, Jona; Lockhofen, Denise; Steinmann, Saskia; Leicht, Gregor; Mulert, Christoph (Frontiers in Neuroscience, 2024)
IntroductionDichotic listening (DL) has been extensively used as a task to investigate auditory processing and hemispheric lateralisation in humans. According to the “callosal relay model,” the typical finding of a right ear advantage (REA) occurs because the information coming from the right ear has direct access to the left dominant hemisphere while the information coming from the left ear has to cross via the corpus callosum. The underlying neuroanatomical correlates and neurophysiological mechanisms have been described using diffusion tensor imaging (DTI) and lagged phase synchronization (LPS) of the interhemispheric auditory pathway. During the non-forced condition of DL, functional connectivity (LPS) of interhemispheric gamma-band coupling has been described as a relevant mechanism related to auditory perception in DL. In this study, we aimed to extend the previous results by exploring the effects of top-down modulation of DL (forced-attention condition) on interhemispheric gamma-band LPS.MethodsRight-handed healthy participants (n = 31; 17 females) performed three blocks of DL with different attention instructions (no-attention, left-ear attention, right-ear attention) during simultaneous EEG recording with 64 channels. Source analysis was done with exact low-resolution brain electromagnetic tomography (eLORETA) and functional connectivity between bilateral auditory areas was assessed as LPS in the gamma-band frequency range.ResultsTwenty-four participants (77%) exhibited a right-ear advantage in the no-attention block. The left- and right-attention conditions significantly decreased and increased right-ear reports, respectively. Similar to the previous studies, functional connectivity analysis (gamma-band LPS) showed significantly increased connectivity between left and right Brodmann areas (BAs) 41 and 42 during left ear reports in contrast with right ear reports. Our new findings notably indicated that the right-attention condition exhibited significantly higher connectivity between BAs 42 compared with the no-attention condition. This enhancement of connectivity was more pronounced during the perception of right ear reports.DiscussionOur results are in line with previous reports describing gamma-band synchronization as a relevant neurophysiological mechanism involved in the interhemispheric connectivity according to the callosal relay model. Moreover, we newly added some evidence of attentional effects on this interhemispheric connectivity, consistent with the attention-executive model. Our results suggest that reciprocal inhibition could be involved in hemispheric lateralization processes.